1995
DOI: 10.1002/mc.2940130408
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immortality: A late event in the progression of human squamous cell carcinoma of the head and neck associated with p53 alteration and a high frequency of allele loss

Abstract: Many human tumors contain variant cells that, unlike their normal counterparts, possess indefinite proliferative potential in vitro. However, little is known of the relevance of these immortal cells to human carcinomas in vivo. To investigate immortality in a human tumor system, we established cultures from different stages of head and neck squamous carcinoma (SCC-HN). All the neoplastic cultures were transformed because they showed very low cornification in surface or suspension culture and were partially or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 37 publications
8
119
0
Order By: Relevance
“…We are con®dent that the changes observed did not occur in vitro because we used a culture system where malignant keratinocytes remain phenotypically stable for more than 200 population doublings (Rheinwald and Beckett, 1981) and we always perform genetic analysis on the cultures when they have completed 30 ± 50 population doublings without any observed slowed proliferation or crisis (Loughran et al, 1994;Edington et al, 1995). Furthermore, we tested lines BICR 3 and BICR 63 for LOH at several loci on chromosomes 1, 4, 6 and 7 at 30 population doublings and again at 130 population doublings and found them still to be heterozygous (data not shown), thus illustrating the genetic stability of the lines during this period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We are con®dent that the changes observed did not occur in vitro because we used a culture system where malignant keratinocytes remain phenotypically stable for more than 200 population doublings (Rheinwald and Beckett, 1981) and we always perform genetic analysis on the cultures when they have completed 30 ± 50 population doublings without any observed slowed proliferation or crisis (Loughran et al, 1994;Edington et al, 1995). Furthermore, we tested lines BICR 3 and BICR 63 for LOH at several loci on chromosomes 1, 4, 6 and 7 at 30 population doublings and again at 130 population doublings and found them still to be heterozygous (data not shown), thus illustrating the genetic stability of the lines during this period.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the process involves one or more recessive inactivating mutations. Two candidates are the p53 and the CDKN2A/p16 ink4A genes which are both inactivated or deleted in immortal but not usually in replicatively senescent neoplastic keratinocytes (Burns et al, 1993Edington et al, 1995;Loughran et al, 1994Loughran et al, , 1996 and we have suggested that the loss of these two suppressor genes in concert is a necessary but insu cient condition to sustain the immortal keratinocyte phenotype in human SCC-HN (Loughran et al, 1994(Loughran et al, , 1996.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…As telomerase is inactivated before or soon after birth , telomeric attrition is experienced by all normal somatic cells studied and has been suggested as a mechanism by which human cells count replication events and limit their clonal proliferation by replicative senescence (Harley et al, 1990). The presence of telomerase in immortal human cell populations and malignant tumours and its general absence prior to this stage, has led to the suggestion that cellular immortalization and telomerase reactivation are essential for the progression and clinical lethality of most human tumours, but not for their formation (Edington et al, 1995;Kim et al, 1994).…”
Section: Introductionmentioning
confidence: 99%